Toxicidade e ação antitumoral in vivo do 4-(4-nitrobenzoato)-piperinoato de butila, um novo derivado da piperina - Ferreira, Rafael Carlos (2019)
Cancer is characterized mainly by the uncontrolled proliferation of cells that have undergone genetic and/or epigenetic changes. Chemotherapy, one of the main treatment modalities for this disease, is associated with the emergence of resistance and significant adverse effects. Thinking about that, several molecules have been synthesized, aiming at the development of more effective drugs and/or with less toxicity. Piperine, an alkaloid found in plants of the genus Piper, has significant antitumor activity. However, this molecule is associated with significant toxicity. Thus, in order to potentiate the antitumor effect and/or reduce the toxicity of piperine, the inedited derivative butyl 4- (4-nitrobenzoate)-piperinoate (DE-07) was synthesized. The aim of this study was to evaluate the in vivo antitumor activity and non clinical toxicity of DE-07. In the acute toxicity test, treatment with doses of 300 and 2000 mg/kg intraperitoneally (i.p.) allowed the estimated mean lethal dose (LD50) to be estimated at approximately 1000 mg/kg. The use of the fish embryo toxicity test (FET test) indicated that the mean lethal concentration (LC50) of DE-07 is greater than 100 μg/mL. The exposure of zebrafish embryos/larvae to DE-07 did not show changes in the lethality indicators evaluated. Treatment with DE-07 (300 mg/kg, i.p.) did not increase the frequency of micronucleated erythrocytes in peripheral blood of Swiss mice. The evaluation of the antitumor activity, using Ehrlich ascitic carcinoma (CAE), showed a significant reduction in viability and total cell parameters. In the evaluation of possible antitumor mechanisms of action, treatment with DE-07 (50 mg/kg, i.p.) showed a significant reduction in peritoneal vascular microdensity, a significant increase in reactive oxygen species (ROS) and a significant increase in IL-1β, TNF-α and IL-4. Assessment of toxicity after treatment with DE-07 did not show changes in heart, liver, kidney, spleen and thymus indices. Reduction in water and feed intake was observed, but there was no significant change in weight evaluation. Discrete histological changes in the liver were evidenced. Reduction of serum aspartate aminotransferase (AST) activity was also observed, but within normal values for the species. Histological analysis of the kidneys did not show any morphological alterations in these organs and, corroborating these results, no significant alterations were observed in the serum concentrations of urea and creatinine. Regarding hematological parameters, leukocytosis was observed, accompanied by lymphocytosis, which, in turn, is within the range of normality for the species. In addition, an increase in hematocrit (HCT) was observed, which was not accompanied by changes in the other parameters of the erythrogram and, therefore, has no clinical significance. These results allow us to infer that DE-07 has low non clinical toxicity and significant in vivo antitumor activity because it induces antiangiogenic, oxidative and modulation of the inflammatory response in the tumor microenvironment effects.